Elite rowers demonstrate consistent patterns of hip cartilage damage compared with matched controls - Bittersohl, B.; Benedikter, C.; Franz, A.; Hesper, T.; Schleich, C.; Antoch, G.; Hosalkar, H.; Harish, S.; Krauspe, R.; Zilkens, C. (Clinical Orthopaedics and Related Research, 2018)
Background: Rowing exposes the femoral head and acetabulum to high levels of repetitive abutment motion and axial loading that may put elite athletes at an increased risk for developing early hip osteoarthritis.